2022
DOI: 10.1139/apnm-2021-0470
|View full text |Cite
|
Sign up to set email alerts
|

Brave spaces: Indigenous children in Canada plan for a different tomorrow

Abstract: When considering the impacts of historical trauma and colonization upon the lived realities of Indigenous young people within Canada, it is essential that research uses strengths-based, capacity building approaches to ensure that the voices are heard and that their perspectives and advice can be actioned. A series of participatory workshops with adults and children were conducted within urban geographies to explore health seeking behaviours, health knowledge, and community resiliency. Research took place in Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
25
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(25 citation statements)
references
References 30 publications
0
25
0
Order By: Relevance
“…As such, we have identified the 16 articles that reported Indigenous personage among their authors (Aparicio et al, 2021; Banyard et al, 2020; Edwards et al, 2022; Faircloth et al, 2016; Genius et al, 2015; Goodman et al, 2018; Hatala et al, 2020; Helm et al, 2015; Hudson et al, 2020; Jennings & Lowe, 2013; Johnson et al, 2020; Jones et al, 2013; Lines & Jardine, 2019; McHugh et al, 2013; Sloan Morgan et al, 2022; Young et al, 2013) to allow our readers to assess where Indigenous perspectives on Photovoice’s effectiveness may be present. Twenty studies did not report on their authorship composition (Cooper, 2022; Cueva et al, 2020; Goodman et al, 2019; Hanemaayer et al, 2022; Jardine & James, 2012; Jennings et al, 2020; Johnston et al, 2012; Kaplun et al, 2016; Kelly, 2017; Liew et al, 2022; Markus, 2012; Minthorn & Marsh, 2016; Philip et al, 2022; Savuro et al, 2022; Shea J et al, 2011; Tremblay et al, 2018; Uchima et al, 2021; Victor et al, 2022; Weinronk et al, 2018; Williamson et al, 2020), and one study reported authorship without any Indigenous identification (Hayhurst et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As such, we have identified the 16 articles that reported Indigenous personage among their authors (Aparicio et al, 2021; Banyard et al, 2020; Edwards et al, 2022; Faircloth et al, 2016; Genius et al, 2015; Goodman et al, 2018; Hatala et al, 2020; Helm et al, 2015; Hudson et al, 2020; Jennings & Lowe, 2013; Johnson et al, 2020; Jones et al, 2013; Lines & Jardine, 2019; McHugh et al, 2013; Sloan Morgan et al, 2022; Young et al, 2013) to allow our readers to assess where Indigenous perspectives on Photovoice’s effectiveness may be present. Twenty studies did not report on their authorship composition (Cooper, 2022; Cueva et al, 2020; Goodman et al, 2019; Hanemaayer et al, 2022; Jardine & James, 2012; Jennings et al, 2020; Johnston et al, 2012; Kaplun et al, 2016; Kelly, 2017; Liew et al, 2022; Markus, 2012; Minthorn & Marsh, 2016; Philip et al, 2022; Savuro et al, 2022; Shea J et al, 2011; Tremblay et al, 2018; Uchima et al, 2021; Victor et al, 2022; Weinronk et al, 2018; Williamson et al, 2020), and one study reported authorship without any Indigenous identification (Hayhurst et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Most studies used Photovoice qualitative methodologies only (Aparicio et al, 2021; Banyard et al, 2020; Cueva et al, 2020; Edwards et al, 2022; Faircloth et al, 2016; Genius et al, 2015; Goodman et al, 2019; Hanemaayer et al, 2020; Hatala et al, 2020; Hayhurst et al, 2015; Helm et al, 2015; Hudson et al, 2020; Jardine & James, 2012; Jennings & Lowe, 2013; Jennings et al, 2020; Johnson et al, 2020; Johnston et al, 2012; Kelly, 2017; Liew et al, 2022; McHugh et al, 2013; Minthorn & Marsh, 2016; Savuro et al, 2022; Shea J et al, 2011; Sloan Morgan et al, 2022; Tremblay et al, 2018; Weinronk et al, 2018; Williamson et al, 2020; Young et al, 2013). A small number used mixed methods (Cooper, 2022; Lines & Jardine, 2019; Markus, 2012; Philip et al, 2022) (Goodman et al, 2018; Jones et al, 2013; Kaplun et al, 2016; Lines & Jardine, 2019; Uchima et al, 2021; Victor et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…Ten research articles are included in the collection, all which have free access (Blanchet et al 2022;Blekkenhorst et al 2022;Cooper 2022;Ferreira et al 2022;Ironside et al 2021;McKay and Godrich 2021;McEachern et al 2022;Robidoux et al 2021;Senftleber et al 2021;Valaitis et al 2022; the main collection page can be accessed here: https://cdnscience pub.com/topic/apnm-strength-based). These articles discuss health research with Indigenous populations in Australia, Canada, and Greenland, high-income countries where Indigenous peoples have experienced European colonialism.…”
mentioning
confidence: 99%
“…These articles discuss health research with Indigenous populations in Australia, Canada, and Greenland, high-income countries where Indigenous peoples have experienced European colonialism. One article presents a current opinion of Indigenous women's worldview of food-related research in Canada (Ferreira et al 2022), five articles address a diversity of decolonizing health promotion research in Canada (Blanchet et al 2022;Cooper 2022;McEachern et al 2022;Robidoux et al 2021;Valaitis et al 2022), one article describes the relationship between social determinants and physical activity among Indigenous adults in Canada (Ironside et al 2021), two review articles summarize health interventions in Australia (Blekkenhorst et al 2022;McKay and Godrich 2021), and one review article describes the role of genetics and lifestyle changes on metabolic health in Inuit in Greenland, since colonization (Senftleber et al 2021). Most articles have Indigenous authors to ensure an Indigenous perspective.…”
mentioning
confidence: 99%
See 1 more Smart Citation